Pengaruh Model Pembelajaran Talking Stick terhadap Keaktifan Belajar Siswa - Pour, Agustina Novitasari; Herayanti, Lovy; Sukroyanti, Baiq Azmi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: The Effect of a Talking Stick Learning Model on Student Learning Activities]. A fun learning environment, active and meaningful for students need to be created by applying active learning model for students that learning model talking stick. This type of research is quasi-experimental. This research aimed to know there is or no effect of talking stick learning model toward students learning activeness. This research implemented in class VIII SMP Negeri 5 Mataram in academic year 2015/2016 from March to April 2016. The technique of sample using cluster random sampling, in order to obtain first-class VIII I totalling 30 students as an experimental class and class VIII E totalling 30 students as the control class. The results of this research are students’ activeness learning showed by using the instrument is activeness of student learning questionnaire. Based on data analysis showed that t-test was 8.28 and t- table was 2.000 (df = 58). So, t-test > t-table (8.28 > 2.000). This means that there is an effect of talking stick learning model toward students learning activeness.